T-t Evolution of the Early Proterozoic Rocks in the Northern Ladoga Region from the Data on U-Pb, Rb-Sr and Sm-Nd Systems in Minerals - Sh. K. Baltybaev; V. M. Savatenkov; M. E. Petrakova (Геодинамика и тектонофизика)
This paper presents the results of a study of isotopic systems in minerals and rocks in southern margin of the epi-Archean Karelian craton in the zone of its junction with the Svecofennian mobile belt. U-Pb, Sm-Nd and Rb-Sr mineral ages of metamorphic rocks allowed reconstructing a T-t trend during ~1.88–1.61 Ga, which reflects a wide-ranging cooling history of metamorphic rocks from the peak values of about 650–700 °C at 1.88–1.79 Ga (U-Pb age of monazites and apparent oldest Sm-Nd age of amphiboles) to 300–400 °C at 1.61 Ga (model Rb-Sr age of biotites) in zones of low- and medium-temperature metamorphism. The specificity of removal of deep-seated rocks to the present-day erosion surface and the reconstructed T-t trend comply with the development of thrust-nappe structures during the exhumation of the Svecofennids. It is also assumed that differential vertical block movements played a significant role during the post-orogenic extensional collapse and neorifting.